Boundary spanner closeness to partner firm as relational governance in turbulent versus stable environments. (10th December 2021) - Cai, Shaohan; Wang, Xiaoyan; Ma, Yongchao; Zhou, Xinyue; Yang, Zhilin
Abstract : Purpose: This study aims to explore the overall relationship between a boundary spanner and a partner firm, i.e. boundary spanner closeness to partner firm. Drawing on consumer-service provider relationship literature and the tripartite model of affect-behavior-cognition, the authors identify three key dimensions of such closeness, namely, boundary spanners' relational ties, customer-specific capabilities and accommodative behaviors, and examine their effects on exchange outcomes in turbulent versus stable environments. Design/methodology/approach: The paper examines the effects of three dimensions of boundary spanner closeness on various exchange outcomes (i.e. retailers' cooperation, satisfaction and willingness for investment) using two industries as exemplars, characterized by distinct levels of environmental turbulence – the retailing networks of a major cell phone company and a petroleum company in China. Findings: The results indicate that the three dimensions individually and jointly affect exchange outcomes and the interplay of customer-specific capabilities and relational ties affect exchange outcomes differently across industry turbulence. Originality/value: The existing literature lacks a comprehensive understanding of the function of boundary spanners, which serve as a key relational interorganizational governance component. By identifying three key dimensions of boundary spanner closeness and examining their effectiveness in promoting exchange outcomes, this study advances the understanding of the role of boundary spanners in interorganizational governance.